MYD88 L265P mutation detected by digital PCR as a prognostic factor in patients with diffuse large B-cell lymphoma in rituximab era. (October 2020) - Nishimura, Noriko; Takeuchi, Kengo; Asaka, Reimi; Tuyama, Naoko; Inoue, Norihito; Kusano, Yoshiharu; Mishima, Yuko; Yokoyama, Masahiro; Terui, Yasuhito
Highlights: Mutations in MYD88 L265 P at diagnosis is an independent prognostic factor of the CNS relapse in patient with diffuse large B-cell lymphoma. Digital PCR detection of the mutation is crucial as a predictor. The MYD88 L265 P mutations were found in patients, predominantly in those with a non-GC subtype, CD5-positive. Abstract: The central nervous system (CNS) relapse in patients with diffuse large B cell lymphoma (DLBCL) is fatal as there are no effective rescue treatments. To test if the presence of the MYD88 L265P mutation is a prognostic factor for secondary CNS relapse, we carried out the digital PCR analysis of 134 samples from patients with DLBCL at diagnosis. The MYD88 L265P mutations were detected in 22 (16.4%) patients, particularly in those with a non-GC subtype, CD5-positive, high absolute monocyte count, extra-nodal lymphoma, and B symptoms. Nine patients showed low signal in digital PCR but were deemed positive for the MYD88 L265P mutation by the nested allele-specific PCR. The remaining 103 patients were negative according to the results of both the PCR analyses. With a median follow-up period of 64 months, the carriers of MYD88 L265P mutation exhibited inferior CNS relapse-free survival at 5 years (53.2% versus 96% and 100%, respectively, P < 0.001) with a significant effect of the mutation demonstrated by the multivariate analysis (hazard ratio 5.1; 95% CI 1.2-22.9, P = 0.02). This suggests that the MYD88 L265P mutation plays a critical role in the progression of DLBCL to CNS.